Burned by leverage? Flows and fragility in bond mutual funds - Luis Molestina Vivar; Michael Wedow; Christian P. Weistroffer (European Central Bank (ECB), 2020)
Does leverage drive investor ows in bond mutual funds? Leverage can increase fund returns in good times, but it can also magnify investors' losses and their response to bad performance. We study bond fund ows to provide new evidence for the link between mutual fund leverage and financial fragility. We find that out ows are greater in leveraged funds during stressed periods and after bad performance, compared with unleveraged funds. We provide supporting evidence that leverage exacerbates the negative externality in investors' redemption decisions. In this regard, we find that fund managers in leveraged funds react more procyclically to net out ows compared with fund managers in unleveraged funds. Such procyclical security sales in leveraged funds may increase investors' first-mover advantages and their response to bad performance. These findings suggest that leverage amplifies fragility in the bond mutual fund sector.
Keywords: G01; G20; G23; 330; bond funds; fund leverage; financial fragility